2012
DOI: 10.1007/s10439-012-0634-0
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic System for Facilitated Quantification of Nanoparticle Accumulation to Cells Under Laminar Flow

Abstract: The identification of novel, synthetic targeting ligands to endothelial receptors has led to the rapid development of targeted nanoparticles for drug, gene and imaging probe delivery. Central to development and optimization are effective models for assessing particle binding in vitro. Here, we developed a simple and cost effective method to quantitatively assess nanoparticle accumulation under physiologically-relevant laminar flow. We designed reversibly vacuum–sealed PDMS microfluidic chambers compatible with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…27 Based on the cell viability determined in the various assays, NP concentrations of 12.5 to 25 µg / mL were used in further studies. The images presented in Figure 1 E 16,32 and enhanced the accumulation of liposomes targeted to vascular cell adhesion molecule-(VCAM-) 1 and also non-targeted nanoparticles in endothelial cells, 32,33 nanoparticle-cell interactions were explored under physiological medium flow conditions. The cartoon in Figure 2 A shows the movement of the added NPs across the cells under flow conditions.…”
Section: Resultsmentioning
confidence: 99%
“…27 Based on the cell viability determined in the various assays, NP concentrations of 12.5 to 25 µg / mL were used in further studies. The images presented in Figure 1 E 16,32 and enhanced the accumulation of liposomes targeted to vascular cell adhesion molecule-(VCAM-) 1 and also non-targeted nanoparticles in endothelial cells, 32,33 nanoparticle-cell interactions were explored under physiological medium flow conditions. The cartoon in Figure 2 A shows the movement of the added NPs across the cells under flow conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As standard in vitro models operate under static conditions, fluid dynamic variations to NP and cellular behavior are neglected in these models. Preliminary work has identified that the introduction of dynamic flow modified cellular morphology, NP behavior, and NP dosimetry (Breitner et al 2015;Kusunose et al 2013;Ucciferri et al 2014). These results suggest that the nano-cellular interface and the rate of NP deposition will be influenced by dynamic flow; making it a critical variable to include during AuNP application analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, relative binding avidity of HUVEC for targeted and nontargeted liposomes in the range of the ligand concentrations was explored according to [34]. Activated or non-activated cells were incubated with the formulations under endocytosis-blocking conditions (at 4°C); then, the cells were allowed to consume surface-bound liposomes (at 37°C) and were analysed by FACS.…”
Section: Accumulation Of Liposomes By Huvecmentioning
confidence: 99%
“…Relative binding avidity was assessed according to [34] as follows: cells were chilled to 4°C, washed with cold DPBS and incubated for 1 h on ice with 2% SiaLe X or control liposomes (50 μM total lipid, 200 μL serum-free medium), then rinsed 3 times with DPBS, treated with 500 μL of complete medium and incubated for 1 h at 37°C. Cells were then rinsed with DPBS, detached with EDTA solution (10 min 37°C) and analysed by FACS.…”
Section: Accumulation Of Liposomes By Huvecmentioning
confidence: 99%